Effect of handlebar height on lower-limb biomechanics and upper body kinematics in elite pursuit cyclists - Williams, D.; Dunn, M.; Worsfold, P.; Newton, D.; Faulkner, S. H.; d'Andrea, F.; Wheat, J. (ISBS Proceedings Archive: Vol. 43: Iss. 1, 2025)
The purpose of this study was to investigate the effect of handlebar height changes on upper body posture and lower-limb biomechanics in elite pursuit cyclists. Sixteen (9 male, 7 female) cyclists completed 1-minute cycling bouts with different handlebar heights (Preferred, -30 mm and +30 mm). 2D motion capture was used to record upper and lower body joint kinematics and integrated with instrumented force pedals to measure crank and lower limb joint kinetics. A general linear mixed model and repeated measures ANOVA were used to assess discrete and time-series variables. The findings indicate that elite cyclists can adapt ankle and hip biomechanics to maintain external force application and power output despite altered upper body posture due to a reduced handlebar height. Therefore, cyclists should consider reducing handlebar height for an aerodynamic gain.